Progress of carbon-based electrodes in microbial fuel cells: A comprehensive review - Tigist Merga; Gebrehiwot Gebreslassie; Tesfu Hailu; A.C. Nwanya; F.I. Ezema; P.M. Ejikeme; Getachew Adam Workneh (Results in Chemistry)
Microbial fuel cells (MFCs) have emerged as a promising technology for sustainable energy production, offering the dual benefits of electricity generation and wastewater treatment. By harnessing the metabolic activity of electroactive microorganisms during substrate oxidation, MFCs convert chemical energy into electrical energy. However, despite their potential, the practical implementation of MFCs is significantly hindered by their relatively low power output. Among the various components of an MFCs, the anode plays a pivotal role not only as the primary site for electron collection from microbial metabolism but also as a surface for biofilm formation. The inadequate performance of conventional anode materials remains a critical limitation, underscoring the need for enhanced electrode designs. In recent years, carbon-based materials have garnered significant attention due to their favorable properties, including high conductivity, chemical stability, and biocompatibility. This review provides a comprehensive overview of the fundamental working principles of MFCs, with a particular focus on advancements in carbonaceous anode materials. Various modification strategies aimed at improving the electrochemical and biological performance of carbon-based electrodes are critically analyzed. Finally, the review highlights current challenges and outlines future research directions to facilitate the practical deployment of MFCs for simultaneous wastewater treatment and renewable energy generation.